Proposition of Belief and Practice Theory for Men Undergoing Infertility Treatment: A Hospital Based Study in Mumbai, India - Baranwal, Anshu; Chattopadhyay, Aparajita (Frontiers in Sociology, 2020)
The paper aims to understand the treatment seeking behavior and the experiences of men with male factor infertility. A cross-sectional study was conducted at consented hospitals/ infertility centers in Mumbai, Indiain purview of the fact that men are not considered as an important part of infertility treatment as of women. An infertile man is defined here as one, who is diagnosed with primary or secondary infertility, undergoing infertility treatment, irrespective of the fertility status of wife. Primary data of 150 men undergoing infertility treatment from a variety of socioeconomic backgrounds, was collected through semi structured interviews. The initial effect of the infertility status led the men feel depressed, guilty, shocking and isolated. A large proportion of the respondents never discussed about the problem with anyone except their wives.More than one third of the respondents consulted with Ayurvedic, Unani, Siddha, and Homeopathy (AYUSH) practitioners . Change of doctors or clinics were more attributed to unsuccessful treatment cycles and success rate of other clinics than the referral by doctors. Destiny, bad luck, lifestyle, medical reasons, late marriage are found as perceived causes of male infertility. Age above 40, younger age at marriage, marriage duration for 6 and more years, secondary infertility, self-employement, higher income have significant association with longer time gap between marriage and initiation of infertility treatment. Based on study findings, we propose Belief and Practice theory where we elaborate the progression in treatment for male infertility. Men should be given due importance in infertility treatment. They must be taken into consideration at an early stage of fertility evaluation due to the fact that minor problems of male infertility can be cured with modest medication. Proper Information Education and Communication (IEC)is essential for creating awareness in society on male infertility. Better counseling services during treatment and standardization of cost can help infertile men to manage treatment related stress. Since Infertility treatment is a time consuming and exhaustive process, considering the timing for patient’s income generating work, evening out patient department and comprehensive knowledge dissemination at health centre can be made essential for betterment of male facor infertility treatment.